Penguatan Peran Takmir Muhammadiyah Se Kabupaten Malang dalam Pemberdayaan Komunitas Keagamaan - Murdiono, Murdiono; Muhammad Yusuf (Edujavare Publishing, 2024)
This service aims to increase the role of Malang Regency Muhammadiyah mosque administrators (takmir) in strengthening religious communities through optimizing management skills. This service method uses a Participatory Rural Appraisal (PRA) approach through holding training sessions, workshops, and management skills development programs for Takmir. The results of this service show an increase in the quality of mosque services, increased community participation in religious activities, and overall empowerment of religious communities. The takmirs succeeded in improving management capabilities in managing the mosque, reflected in implementing more structured and quality religious programs and increased coordination with the surrounding community. Increasing community participation in religious activities also provides significant results; this shows the effectiveness of community service in strengthening active community involvement in religious activities. This service concludes that optimizing Takmir Muhammadiyah's management skills has positively impacted empowering religious communities in Malang Regency. The role of mosques as centers of religious and social activities is increasingly strengthening, while the community is increasingly actively involved in religious activities. This shows that this service has succeeded in achieving its goal, namely strengthening religious communities through improving the management skills of Muhammadiyah Takmir.